COMPARISON OF TWO ROLLING FORECASTING MECHANISMS FOR THREE-ECHELON SUPPLY CHAINS - Huang, Li-Ting; Hung, Shin-Wei (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
Rolling forecast applied for dealing with customers’ requirement of squeezed delivery time is generally discussed in a two-echelon supply chain. Because of a more complicated supply chain in practical, we investigate whether advantages of rolling forecast exist in a three-level supply chain, who derives the most benefits, as well as consider the influence of forecast frozen cycle time. The advantages vary from three rolling forecast information-sharing models built based on reach of information sharing along the supply chain. Supplier chain partners benefit differently from rolling forecast. Results indicate that (1) suppliers benefits very much only when implementing collaborative rolling forecast, (2) the influence of frozen cycle time is positively associated with overall performance, especially when suppliers could directly acquire customers’ rolling forecast data, and (3) increasing the information visibility is critical to overall performance; such is accomplished by transmitting rolling forecast information from customers to all supply chain partners.